Interjeksi Volitif Dalam Bahasa Batak Toba : Kajian Metabahasa Semantik Alami - Lumbantoruan, Sari Rosa Jeli; Mulyadi, Mulyadi; Parlaungan, Parlaungan (Innovative: Journal Of Social Science Research, 2024)
This study outlines the categorization of volitional interjections in the Indonesian language based on their meaning and form. The Natural Semantic Metalanguage theory is applied to analyze and classify volitional interjections according to their meanings. The study identifies categories of volitional interjections grouped by their purposes. The data for this research were collected using the listening method and sourced from various storybooks and novels in the Batak Toba language, such as Sijanggual and Mangongkal Holi. Additionally, some data were obtained from observing conversations among Batak Toba speakers who live and were born in villages inhabited by Batak Toba-speaking communities. Data were also gathered from observing opera videos, short films, or videos depicting the daily activities of Batak Toba-speaking communities. The research results are presented using the distributional method, revealing a total of 27 volitional interjections in the Batak Toba language. These interjections are further explained based on their meanings and categorizations.